Efficacy and safety of ciprofol versus propofol for anesthesia in patients undergoing gastrointestinal endoscope: a systematic review and meta-analysis of randomized controlled trials (RCT) - Zhaoxuan Wang; Siru Wang; Lu Liu; Xiaolu Zhang; Meijuan Ren; Qianqian Zhang; Chang Liu (BMC Anesthesiology)
Abstract Background Ciprofol is considered an alternative to propofol and can be used to achieve anesthesia at a lower dose with a lower incidence of adverse events. The primary objective of this study was to compare the efficacy and safety of ciprofol and propofol used in patients undergoing gastrointestinal endoscopes. Methods The databases of PubMed, Embase, Cochrane Library, Web of Science, and China National Knowledge Infrastructure were retrieved for randomized controlled trials of ciprofol and propofol used in gastrointestinal endoscopes from inception to May 10, 2024. All statistical analyses were conducted using Stata 14.0. Primary outcomes encompassed a successful rate of sedation and other safety outcomes, including injection pain, hypotension, bradycardia, overall respiratory disorders, and hypoxemia. Secondary outcomes concluded time to onset of successful induction, waking time, and discharge time. Results A total of 20 studies were included, involving 3779 patients. The results of the meta-analysis showed that the successful rate of anesthesia and waking time were not significantly different between ciprofol and propofol, while ciprofol was better than propofol in injection pain (RR: 0.10, 95% CI: 0.07 to 0.16, p < 0.001, I2 = 46.4%, moderate certainty), hypotension (RR: 0.68, 95% CI: 0.59 to 0.77, p < 0.001, I2 = 49.2%, moderate certainty), bradycardia (RR: 0.67, 95% CI: 0.52 to 0.85, p = 0.001, I2 = 0.0%, moderate certainty), hypoxemia (RR: 0.45, 95% CI: 0.33 to 0.61, p < 0.001, I2 = 9.2%, moderate certainty), and overall respiratory disorders (RR: 0.45, 95% CI: 0.27 to 0.75, p < 0.001, I2 = 77.1%, moderate certainty). In addition, compared to propofol, shorter time to onset of successful induction (MD: -0.16, 95% CI: -0.24 to − 0.08, p < 0.001, I2 = 97.2%, very low certainty) and longer discharge time (MD: 0.420, 95% CI: 0.29 to 0.54, p < 0.001, I2 = 29.4%, moderate certainty) were related to ciprofol. Conclusion Based on the results of pooled analysis, we conclude that ciprofol takes longer for cipofol to recover after surgery, it may greatly improve the pain problem and hemodynamic stability of intravenous propofol. Therefore, we believe that ciprofol can be used as an excellent substitute for propofol.